Development Strategy for Household Sugar Industry in Lamanu Village, Kabawo District, Muna Regency - Suprin Suprin; Sarinah Sarinah; Muhammad Sukri Sadimantara (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
The home industry has an important role in the absorption of labor, income distribution, and improving people's welfare. Palm sugar home industry in Lamnu Village, Kabawo District, Muna Regency. The problem in this study is how to develop a palm sugar home industry strategy in Lamnu Village, Kabawo District, Muna Regency. The aim of this research is to find out how the strategy for developing the small sugar industry is. Palm sugar industry in Lamnu village, Kabawo district, Muna district. The population in this study were all 11 palm sugar managers. Sampling in this study used the accidental sampling method by selecting a sample of 1 respondents. The strategy applied is more defensive in nature, namely avoiding lost sales. , namely avoiding lost sales and lost profits caused by threats. The advice given is to maintain the characteristic taste of the product and improve product quality by creating innovations in product packaging, adding product types to have a high attractiveness in order to remain able to compete with other products.